A Multifaceted Ferrocene Interlayer for Highly Stable and Efficient Lithium Doped Spiro‐OMeTAD‐based Perovskite Solar Cells. Issue 26 (20th May 2022) - Webb, Thomas; Liu, Xueping; Westbrook, Robert J.E.; Kern, Stefanie; Sajjad, Muhammad T.; Jenatsch, Sandra; Jayawardena, K. D. G. Imalka; Perera, W. Hashini K.; Marko, Igor P.; Sathasivam, Sanjayan; Li, Bowei; Yavari, Mozhgan; et al.
Abstract: Over the last decade, 2, 2″, 7, 7″‐Tetrakis[ N, N ‐di(4‐methoxyphenyl)amino]‐9, 9′‐spirobifluorene (spiro‐OMeTAD) has remained the hole transporting layer (HTL) of choice for producing high efficiency perovskite solar cells (PSCs). However, PSCs incorporating spiro‐OMeTAD suffer significantly from dopant induced instability and non‐ideal band alignments. Herein, a new approach is presented for tackling these issues using the functionality of organometallocenes to bind to Li + dopant ions, rendering them immobile and reducing their impact on the degradation of PSCs. Consequently, significant improvements are observed in device stability under elevated temperature and humidity, conditions in which ion migration occurs most readily. Remarkably, PSCs prepared with ferrocene retain 70% of the initial power conversion efficiency (PCE) after a period of 1250 h as compared to only 8% in the control. Synergistically, it is also identified that ferrocene improves the hole extraction yield at the HTL interface and reduces interfacial recombination enabling PCEs to reach 23.45%. This work offers a pathway for producing highly efficient spiro‐OMeTAD devices with conventional dopants via addressing the key challenge of dopant induced instability in leading PSCs. Abstract : The doping of LiTFSI into highly efficient spiro‐OMeTAD‐based PSCs severely compromises the device stability via migration of Li + into the perovskite. Here, ferrocene is used to bind to the lithium cations limiting their ability to migrate. This strategy significantly enhances the stability of resulting devices while also improving hole extraction across the perovskite/spiro‐OMeTAD interface.